Quality of supervision: postgraduate dental research trainees' perspectives. (6th January 2015) - Beaudin, A.; Emami, E.; Palumbo, M.; Tran, S. D.
Abstract: Introduction: Supervision is a pillar in enhancing the student's learning environment throughout her/his higher education. Multiple studies qualify graduate supervision among the most important contributors to the successful completion of a higher education degree and to graduate students' positive academic experience. The aim of this study was to assess the views of graduate students enrolled in the Dental Sciences and Craniofacial Research Graduate Programs at McGill University ( n  = 64) regarding the quality of supervision they are receiving. Methods and materials: An online questionnaire composed of 22 open and closed‐ended format items was used and covered five domains: student profile, supervisory relationship, conflict resolution, student progress/thesis writing and career development. Descriptive statistics, chi‐square tests and interpretative qualitative analysis were used to evaluate students' perspectives. Results: Fifty‐nine students completed the survey (92.2%). The distribution of sample in regard to the graduate student level was almost identical (M.Sc. level n  = 28, Ph.D. n  = 31). Overall, most graduate students appeared satisfied with the supervision they received and had similar perspectives about the surveyed domains. There was one statistically significant difference ( P  < 0.05) between MSc and PhD students when asked if their supervisors aided them in career development outside the supervisory relationship, where 77.4% ( n  = 24) of doctoral students agreed as opposed to 21.4% ( n  = 12) of Masters' students. Conclusions: Our results showed that McGill graduate students appeared to be overall satisfied with the supervision they received. The main elements contributing to a positive supervision experience were support, guidance, availability and good communication between supervisees and supervisors.